Bulk organic matter δ13C, biomarker, and microfossil radiocarbon data of cores PS51/154-11 and PS51/159-10 from the Laptev Sea, Arctic Ocean - Tsai-Wen Lin; Tommaso Tesi; Jens Hefter; Hendrik Grotheer; Jutta Erika Wollenburg; Gesine Mollenhauer (PANGAEA, 2025)
The data were obtained from cores PS51/154-11 (77.276000°N, 120.609833°W; 270 m) and PS51/159-10 (76.766667°N, 116.031667°W; 60 m) in the western Laptev Sea. Sediments were subsampled from the cores with 10 mL syringes in 5–10 cm intervals. The dataset includes: 1) stable carbon isotope ratio (δ13C) from bulk organic matter; 2) additional radiocarbon measurements on microfossils; and 3) biomarker indices, including the n-alkane based Carbon Preference Index (CPI), the Sphagnum proxy (C25/(C25+C29) ratio), the syringyl phenols to vanillyl phenols ratio (S/V), the cinnamyl phenols to vanillyl phenols ratio (C/V), the vanillic acid to vanillin ratio (Vd/Vl), and the mass accumulation rate of high molecular weight fatty acids (C24:0+C26:0+C28:0+C30:0, HMW fatty acid MAR).